Human resources management issues, challenges and trends : "now and around the corner" - Sims, Ronald R.; Bias, Sheri K. (Contemporary human resource management., 2019)
Human Resources Management Issues, Challenges and Trends: 'Now and Around the Corner' explores and provides an updated look at some of the challenges, trends and issues HRM professionals will need to focus on now and around the corner. Like other departments in the broader organization HRM professionals will need to increasingly demonstrate how they add value and contribute to the organization's success. While the trends, challenges and issues impacting organizations and HRM professionals will continue to change over the years, the bottom-line of organization success is the clear reality that employees are their best assets and the need for effective HRM.The book is intended to help to better understand the ongoing transformation of HRM given the issues, challenges and opportunities offered by the contributors to this book. This means the book discusses the ever evolving role of HRM professionals to include discussion of how the profession must continue to become more adaptive, resilient, quick to change direction and customer-centered in its efforts to help meet the human resource needs of contemporary organizations and their employees. The book contributes to the ongoing dialogue and insights offered by HRM experts on what HRM professionals and their organizations can do in the face of such challenges, trends and issues in their efforts to win the talent wars.